2020
DOI: 10.1038/s41598-020-61630-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of highly potent and selective inhibitor, TIPTP, of the p22phox-Rubicon axis as a therapeutic agent for rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease linked to oxidative stress, which is associated with significant morbidity. The NADPH oxidase complex (NOX) produces reactive oxygen species (ROS) that are among the key markers for determining RA's pathophysiology. Therefore, understanding ROS-regulated molecular pathways and their interaction is necessary for developing novel therapeutic approaches for RA. Here, by combining mouse genetics and biochemistry with clinical tissue analysis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…5a , middle panel). CY24A is a sub-component of the superoxide generating NOX2 enzyme on macrophage membrane 33 . In terms of SEVC enriched protein markers, BST2 is known to be highly expressed in blood vessels throughout the body as an intrinsic immunity factor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a , middle panel). CY24A is a sub-component of the superoxide generating NOX2 enzyme on macrophage membrane 33 . In terms of SEVC enriched protein markers, BST2 is known to be highly expressed in blood vessels throughout the body as an intrinsic immunity factor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both an adenovirus encoding a full-length mouse Rubicon and a Rubicon-specific shRNA adenovirus were constructed, as previously described [ 15 ]. The recombinant viruses were amplified in AD-293 cells, purified and concentrated by BD Adeno-X TM purification kit (BD Biosciences, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we recently reported that an N-terminal eight amino acid (N8) peptide derived from p22phox and mimetic of N8, known as 2-(tetrahydroindazolyl)phenoxy- N -(thiadiazolyl) propenamide 2 (TIPTP), exhibits potent anti-inflammatory effects by interrupting the interaction of Rubicon and p22phox. These effects protected mice from acute polymicrobial sepsis induced by a cecal ligation procedure (CLP) and chronic rheumatoid arthritis (RA) [ 14 , 15 ]. Thus, these compounds may represent an essential resource for the development of therapeutics against intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…For RAW enriched membrane proteins, CD14 32 and CD68 32, 33 are mainly produced in macrophage cells and widely used as a histochemical or cytochemical marker for inflammation-related macrophages (Figure 5, middle panel). CY24A is a sub-component of the superoxide generating NOX2 enzyme on macrophage membrane 34 . In term of SEVC enriched protein markers, BST2 is known to highly express in blood vessels throughout the body as an intrinsic immunity factor (Figure 5, right panel) 35 .…”
Section: Resultsmentioning
confidence: 99%